1989
DOI: 10.1002/jctb.280460104
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitive action of dimethyltin dichloride towards the corrosion of aluminium in hydrochloric acid and sodium hydroxide solutions

Abstract: The dissolution of aluminium in hydrochloric acid and sodium hydroxide solutions in the presence of dimethyltin dichloride as corrosion inhibitor has been studied using hydrogen evolution and thermometric methods. The two methods gave consistent results. The higher inhibition efficiency of this compound in acidic than in alkaline media may be due to the less negative potential of aluminium in hydrochloric acid solution, favouring adsorption of the additive. The adsorption of this compound was found to obey Fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In 1989, Mourad et al found that dimethyltin dichloride could form an adsorption film on an aluminum surface in a HCl medium, exhibiting effective corrosion inhibition. 28 In view of low toxicity, high stability, functionality of estertin/carboxyltin, and the versatility of POMs, the first single crystal of carboxyethyltin-modified POM was obtained in 2010. 29 After that, sandwich-type tungstoarsenate and tungstogermanate containing carboxyethyltin groups were synthesized and studied as corrosion inhibitors on carbon steel in circulating cooling water systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1989, Mourad et al found that dimethyltin dichloride could form an adsorption film on an aluminum surface in a HCl medium, exhibiting effective corrosion inhibition. 28 In view of low toxicity, high stability, functionality of estertin/carboxyltin, and the versatility of POMs, the first single crystal of carboxyethyltin-modified POM was obtained in 2010. 29 After that, sandwich-type tungstoarsenate and tungstogermanate containing carboxyethyltin groups were synthesized and studied as corrosion inhibitors on carbon steel in circulating cooling water systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 1989, Mourad et al . found that dimethyltin dichloride could form an adsorption film on an aluminum surface in a HCl medium, exhibiting effective corrosion inhibition . In view of low toxicity, high stability, functionality of estertin/carboxyltin, and the versatility of POMs, the first single crystal of carboxyethyltin-modified POM was obtained in 2010 .…”
Section: Introductionmentioning
confidence: 99%